Status Quo And Development Research Of National Enterprises IT Capability - Tao, Li Run (2008)
National enterprise is the lifeline of national economy and the development of national enterprise plays enormous leading role.This paper is to research IT capability theory in view of resource-based theory, research IT capability status quo of enterprise under State-owned Asset Supervision and Management Commission, design a set of complete and scientific enterprise IT capability evaluation index system on the basis of summarizing status quo and put forward advice on national enterprise informatization IT capability development, so as to direct informatization practice.